2018
DOI: 10.1177/0972652717748101
|View full text |Cite
|
Sign up to set email alerts
|

Fund Manager Performance in Emerging Market: Factor Specialisation and Financial Crisis Impact

Abstract: In the branch of literature dealing with analysis of the consistency of management styles, this article investigates the relation between portfolio concentration and the performance of emerging market equity funds. Unlike previous studies, on global and US mutual fund, we focus on emerging markets equity, finding funds with higher levels of tracking error, display lower performance than funds with less diversified portfolios when we do not take into account specific concentration in holdings in different multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…However, this study found that Indian investors who diversified their portfolios performed better than those who concentrated their portfolios. Our result aligns with Galloppo and Aliano (2018), who studied emerging markets. This study was mainly focused on the relationship between manager skills and portfolio concentration, which was found positive in previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, this study found that Indian investors who diversified their portfolios performed better than those who concentrated their portfolios. Our result aligns with Galloppo and Aliano (2018), who studied emerging markets. This study was mainly focused on the relationship between manager skills and portfolio concentration, which was found positive in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies found that diversified funds performed better than concentrated funds. Galloppo and Aliano (2018) studied the emerging market and found no evidence supporting the positive relationship between concentration and fund performance.…”
Section: Introductionmentioning
confidence: 98%
“…Results from a study by Barras et al (2006), in which the relatively new false discovery rate was used to assess the performance of unit trusts, may seem disquieting to ordinary investors who are convinced of the advantages of active portfolio management. Other authors scrutinized the performance of over 2,000 mutual funds and came to the conclusion that only 0.6% of these funds proved to actually defeat the market (Barras et al, 2006;Galloppo & Aliano, 2018;Vychytilova, 2018;Sosnowski, 2018). Along with these studies, others have shown similar outcomes in recent years.…”
Section: Introductionmentioning
confidence: 94%
“…Graham et al ., 2020; Banegas et al ., 2013; Engstrom, 2003; Otten and Bams, 2002) and other regions, including some emerging markets (see, e.g. Galloppo and Aliano, 2018; Ferreira et al ., 2013; Huij and Post, 2011; Kaminsky et al ., 2004). Importantly, however, many of these studies highlight the role of market-specific qualitative differences, macroeconomic factors and market efficiency in less developed markets.…”
Section: Background Literaturementioning
confidence: 99%